Identitas Orang yang dipilih Allah: Memaknai Kembali menjadi “Garam Dunia” menurut Matius 5:13 - Sarael, Vivin; Nassa, Grace Son (Sekolah Tinggi Teologi Transformasi Indonesia, 2022)
Abstract: The purpose of this research is to redefine the identity of the person chosen by God based on the concept of